The The Influence of Circle of Friends on Free Sex Behavior Among Adolescents from Highly Educated Families: The Influence of Circle of Friends on Free Sex Behavior Among Adolescents from Highly Educated Families - Cheirunnisa Gunawan; Wahyu ningsih; CintaDwi Cahyani; Ahmad Labiq (Institut Agama Islam (IAI) Nurul Hakim, 2022)
The purpose of this study was to analyze the influence of the role of family and the environment of friendship on premarital sexual behavior in adolescents who have parents with higher education backgrounds. This type of research is descriptive with a quantitative approach. This research was conducted using the method, namely by making a questionnaire related to the statement of adolescent knowledge and the influence of the friendship environment on free sex behavior among adolescents. The target of this research is adolescents aged 16 years and over. Subjects were selected using a systematic random sampling technique. The research sample was 41 adolescents. The unfavorable role of peers and family will greatly affect at-risk adolescents. The results of this study show that to prevent free sex behavior among teenagers in the school environment, it is hoped that the current regulations will be implemented, which were previously mutually agreed upon between the school and parents. In addition, it is important that counseling coupled with the application of character is one thing that schools can do to educate them. Sometimes, children want to express things that make it difficult for them to implement character education or become a good person. Not infrequently children actually have problems at home that interfere with their personality (mentally), affect their behavior and are carried out without considering their feelings and consequences.